Data-driven process discovery and analysis : 4th International Symposium, SIMPDA 2014, Milan, Italy, August 30, 2013, Revised selected papers /: 4th International Symposium, SIMPDA 2014, Milan, Italy, August 30, 2013, Revised selected papers. (2015) - Unknown
No abstract available